Extended urbanisation and the spatialities of infectious disease: Demographic change, infrastructure and governance - Connolly, Creighton; Keil, Roger; Ali, S. Harris (Urban studies (Edinburgh, Scotland), 2021)
This paper argues that contemporary processes of extended urbanisation, which include suburbanisation, post-suburbanisation and peri-urbanisation, may result in increased vulnerability to infectious disease spread. Through a review of existing literature at the nexus of urbanisation and infectious disease, we consider how this (potential) increased vulnerability to infectious diseases in peri– or suburban areas is in fact dialectically related to socio-material transformations on the metropolitan edge. In particular, we highlight three key factors influencing the spread of infectious disease that have been identified in the literature: demographic change, infrastructure and governance. These have been chosen given both the prominence of these themes and their role in shaping the spread of disease on the urban edge. Further, we suggest how a landscape political ecology framework can be useful for examining the role of socioecological transformations in generating increased risk of infectious disease in peri–and suburban areas. To illustrate our arguments we will draw upon examples from various re-emerging infectious disease events and outbreaks around the world to reveal how extended urbanisation in the broadest sense has amplified the conditions necessary for the spread of infectious diseases. We thus call for future research on the spatialities of health and disease to pay attention to how variegated patterns of extended urbanisation may influence possible outbreaks and the mechanisms through which such risks can be alleviated. 本文认为，当代的扩展城市化进程，包括郊区化、后郊区化和周边城市化，可能会导致传染病传播方面脆弱性的增加。通过回顾现有的关于城市化和传染病之间关系的文献，我们研究这种（潜在的 ）周边或郊区传染病脆弱性的增加与大都市边缘的社会物质转变之间是如何辩证相关的。特别是，我们强调了文献中确定的影响传染病传播的三个关键因素：人口变化、基础设施和治理。鉴于这些主题的突出性及其在城市边缘疾病传播中的作用，我们选择了这些主题。此外，我们提出了景观政治生态框架在研究社会生态转变对周边和郊区传染病风险增高的影响方面的作用。为了说明我们的论点，我们将使用世界各地各种重新出现的传染病事件和爆发的例子，揭示了最广以上的城市化扩展如何扩大了传染病传播的必要条件。因此，我们呼吁，在未来对健康和疾病的空间关系的研究中，应关注各种不同的扩展城市化模式对疾病爆发风险的影响，以及减轻这种风险的机制。